Rare RNF213 variants is related to early-onset intracranial atherosclerosis: A Chinese community-based study - Fang, Jianxun; Yang, Xinzhuang; Tang, Mingyu; Li, Shengde; Han, Fei; Zhou, Lixin; Li, Mingli; Yang, Meng; Cui, Liying; Zhang, Shuyang; Zhu, Yicheng; Yao, Ming; et al. (Journal of stroke and cerebrovascular diseases, 2024)
The relationship between rare variants in Ring finger protein 213 (RNF213) and intracranial atherosclerosis (ICAS) remained unelucidated. Using whole-exome sequencing (WES) and high-resolution magnetic resonance imaging (HR-MRI), this study aimed at investigating the association between rare RNF213 variants and ICAS within a Chinese community-dwelling population. The present study included 821 participants from Shunyi cohort. Genetic data of rare RNF213 variants were acquired by WES and were categorized by functional domains. Intracranial and extracranial atherosclerosis were assessed by brain HR-MRI and carotid ultrasound, respectively. Logistic regression and generalized linear regression were applied to evaluate the effects of rare RNF213 variants on atherosclerosis. Stratification by age were conducted with 50 years old set as the cutoff value. Ninety-five participants were identified as carriers of rare RNF213 variants. Carotid plaques were observed in 367 (44.7 %) participants, while ICAS was identified in 306 (37.3 %). Rare variants of RNF213 was not associated with ECAS. Employing HR-MRI, both the presence of rare variants (β = 0.150, P = 0.025) and numerical count of variants (β = 0.182, P = 0.003) were significantly correlated with ICAS within the group of age ≤50 years. Both variant existence (β = 0.154, P = 0.014) and variant count (β = 0.188, P = 0.003) were significantly associated with plaques in middle cerebral arteries within younger subgroup, rather than basilar arteries. Furthermore, a significant association was observed between variants that located outside the N-arm domain and ICAS in the younger subgroup (OR = 2.522, P = 0.030). Statistical results remained robust after adjusted for age, gender, and cardiovascular risk factors. Rare variants of RNF213 is associated with age-related ICAS in general Chinese population, highlighting the potential role of RNF213 as a genetic contributor to early-onset ICAS.